LIDAR-Assisted Feedforward Pitch Control of 15 MW Floating Offshore Wind Turbines - Russell, A; Collu, M; McDonald, A; Thies, P; Mortimer, A; Quayle, A (Volume 8: Ocean Renewable Energy, 2023)
This is the author accepted manuscript. The final version is available from ASME via the DOI in this record Nacelle-mounted, forward-facing Light Detection and Ranging (LIDAR) technology is able to measure the wind field as it approaches a wind turbine. Knowledge of the incoming wind can be used for feedforward turbine control, enabling torque, pitch or yaw systems in advance of the wind’s impact. This can enhance turbine performance through improved rotor speed regulation and power capture, while reducing structural loads. LIDAR has previously exhibited its most significant benefits for turbine performance when assisting with blade pitch control in above-rated wind speed conditions. The impact of feedforward pitch control implementation in floating offshore wind turbines is expected to vary for different substructures due to their differing natural frequencies of motion and rates of feedback pitch control actuation, as a consequence of modified controller gains required to overcome negative damping. This computational study outlines the LIDAR-assisted feedforward pitch control implementation approach, and compares its impacts on two floating substructures supporting the IEA 15 MW reference turbine: the UMaine VolturnUS-S Semi-Submersible and the WindCrete Spar. Under turbulent wind conditions and by using a LIDAR simulator to capture the incoming wind field, both floating turbine configurations benefitted from LIDAR-assisted feedforward pitch control, through improved rotor speed regulation by up to 33%, reduced loads by up to 17% and platform motions by up to 19%. These performance improvements can lead to reduced component failure rates, maintenance, and, ultimately, reduced lifetime operations and maintenance expenditure. Engineering and Physical Sciences Research Council (EPSRC)